WORD WALL TECHNIQUE IN IMPROVING STUDENTS’ VOCABULARY MASTERY AT SMP NEGERI 2 PERCUT SEI TUAN: TEKNIK WORD WALL DALAM MENINGKATKAN PENGUASAAN KOSA KATA SISWA DI SMP NEGERI 2 PERCUT SEI TUAN - Indriyani Wulan Nova, Nazliya (LPPM UPMI, 2024)
This research aims to find out whether the use of the word wall technique can increase students’ vocabulary mastery and students’ interest in learning vocabulary with a word wall. This research was conducted at SMP Negeri 2 Percut Sei Tuan, Deli Serdang Regency for the 2023/2024 academic year. The main problem in this research consisted of 50 students. The form of research is quasi experimental where the research uses two groups, namely,VIII-9 as a control group (not using the word wall technique) with a total of 25 students and VIII-11 as an experimental group (using the word wall technique) with a total of 25 students. The researcher gave a pre-test and post-test for both groups. The results of the data showed that there was an increase and interest in using word wall technique to increase students’ vocabulary. The percentage of students’ scores before being taught using the word wall technique was 19.34% and after teaching using word wall technique was 41.76%. Therefore, the alternative hypothesis (Ha) for this research is accepted. This means that the use of the word wall technique increases students’ vocabulary mastery in class VIII of SMP Negeri 2 Percut Sei Tuan.